Modified Keles TPA –An Effective Method for Molar Derotation - Kallury, Amitabh; Dubey, Jaina; Balani, Rajesh Kumar; Bharti, Chandni (Orthodontic Journal of Nepal, 2020)
Mesio-palatal rotation of maxillary 1st molars is commonly encountered in clinical practice and this results in a Class I molar relation becoming end on. Traditionally transpalatal arches (TPA) fabricated with 0.036” stainless steel wires have been used for correction of molar rotation in fixed orthodontic treatment. They are not very efficient in correcting the mesio-palatal rotations and require frequent activations. This article describes a modified Keles TPA as an easy, effective method for rapid and precise correction of unilateral or bilateral mesio-palatal molar rotations